Innovative use of satellite data from remote sensing and supervised learning to reduce the impact of drought on crop production - CGIAR Research Program on Wheat (2019)
Use of this method is still exploratory, and the paper explores different approaches that could be used. It is the first step towards a process of weather forecasting using machine learning and deep learning algorithms.